Cost-minimization analysis of nifedipine compared to amlodipine in uncomplicated preeclampsia at secondary referral hospital setting - Adila Awaludin; Fina Ahmad Fitriana; Nadhira Alvi Syahrina (Pharmaciana, 2026)
Nifedipine and amlodipine are both used in clinical practice as antihypertensive options for the management of preeclampsia. Although nifedipine is more commonly recommended, amlodipine is also used in practice, and evidence suggest that both offer comparable outcomes. Existing studies on antihypertensive use in preeclamptic patients have primarily focused on clinical outcomes, with limited evaluation from an economic perspective. Therefore, this study applied a cost minimization approach to identify which antihypertensive is more affordable. A cost-minimization analysis was conducted to compare the total cost between nifedipine and amlodipine. A cost analysis was performed using direct medical costs from a healthcare perspective. Data were collected retrospectively from January 2021 to June 2025 using a purposive sampling among uncomplicated preeclampsia patients. In addition to analyzing patient characteristics and average total cost per patient, a one-way sensitivity analysis was also performed. The results showed that the total cost significantly was lower in the nifedipine group compared to the amlodipine group (IDR 1,467,225 vs. IDR 1,938,051). However, the daily cost of amlodipine therapy use was significantly lower than nifedipine. Medication costs accounted for only 3–4% of the total treatment expenses among patients with preeclampsia. Sensitivity analysis confirmed that medical supply and nursing care cost were the most dominant factors influencing the total treatment cost. These findings indicate that nifedipine use in uncomplicated preeclampsia may contribute to overall cost efficiency in patient management.